Violent Narrative Content in Cyber Space: The Case Study of Indonesian Tik Tok’s Short Storytelling Videos - Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2022)
This article focuses on the narrative contents of Indonesian short storyteller in TikTok. TikTok storytelling is one of the forms of literature in cyber space. The aim of the research is to explain about storytelling which contain of violent content by Indonesian TikTok up loaders. The research design applied is qualitative research. The result of the research shows that the TikTok’s short storytelling videos are mostly violent narrative contents which take some themes dealing with the story genre of Indonesian horror, domestic violence, bullying toward children, religious punishment, bad relationship between husband and wife, bad relationship between children and parents, the punishment toward evil person, bad children and bad student. Storytelling in TikTok can affect the viewer’s habit of speaking as they imitate the language used by the content creators in their daily conversation. The viewers include both teenager and underage. Through this research, the next researcher can gain insight literature form development in cyber space and it can be the reference of the study on language variation used by the millennial generation of 5.0 era.